Liechtenstein : Assessment of Financial Sector Supervision and Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The financial sector in Liechtenstein provides primarily wealth-management services, including banking, trust, other fiduciary services, investment management, and life insurance. The establishment of the Financial Market Authority (FMA) as the unified, independent regulator in January 2005 is a huge step for the financial services industry. The FMA and other authorities have been successful in implementing most of the recommendations provided in the earlier 2002 IMF assessment. The authorities and the industry continue to make significant efforts to strengthen the antimoney laundering regime, though there is still work ahead.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet